Clinical-pathological correlation of the acute myocardial infarction at Martin Chang Puga Hospital of Nuevitas. - Arvelio Adán Sánchez; Odelaisis Tamarit Castillo; Juan Antonio Rodríguez Díaz (ECIMED, 2011)
Among cardiovascular diseases the acute myocardial infarction, remainone of the main causes of death in the developed world as well as in developingcountries like Cuba.Objective To determine the behavior of the clinical-pathological correlation in pacientswho died from acute myocardial infarction.Method A traverse, retrospective and descriptive study was carried out aboutthe clinical-pathological correlation in patients who died from acute myocardialinfarction in the period comprehended from january 2000 to december2010, in the Martin Chang Puga Hospital, of Nuevitas.Results The 40,98% of the deceased occurred in the ages between 66 and 75years; the high blood pressure and the smoking habit were the more frequentpersonal pathological antecedents, there was not clinicalpathologicalcorrelation in 29,51% of the patients who died from acutemyocardial infarction.Conclusion It existed a prevalence of the male sex and in the ages from 66 to 75years old; the most frequent complication was the cardiogenic shock anda clinical-pathological correlation was demonstrated in most of the patientsdied from this disease.